Using an ultrasonography risk stratification system to enhance the thyroid fine needle aspiration performance. Issue 150 (May 2022) - Strieder, Débora L.; Cristo, Ana P.; Zanella, André B.; Faccin, Carlo S.; Farenzena, Mauricio; Graudenz, Márcia S.; Dora, José Miguel; Maia, Ana Luiza; Scheffel, Rafael Selbach
Highlights: ACR TI-RADS uses a point summation to stratify malignancy of thyroid nodules. We observed negative predictive value of 97.6% and accuracy of 73.1% for TI-RADS. ACR TI-RADS reduces the number of fine needle aspiration biopsy indications. The false negative rate was 2.3%, but only 7 malignant cases would be missed. TI-RADS significant decrease the number of FNAB and increase diagnostic accuracy. Abstract: Purpouse. The American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI-RADS) is a risk stratification system for thyroid nodules based on their ultrasonography (US) characteristics. Here, we aimed to assess TI-RADS on fine needle aspiration biopsy (FNAB) recommendations and performance in thyroid nodules. Methods: We performed a retrospective study in a single center. All patients with thyroid nodules who underwent FNAB between 2012 and 2019 were included. TI-RADS data were extracted from medical records. Malignancy rates were defined based on cytological exams. Results: A total of 1, 044 nodules (938 patients) were evaluated. TI-RADS classification was as follows: 13 TI-RADS 1, 524 TI-RADS 2, 273 TI-RADS 3, 148 TI-RADS 4, and 85 TI-RADS 5. TI-RADS classification showed a sensitivity of 75% (95 %CI: 63–84.7), a negative predictive value of 97.6% (95 %CI: 96.5–98.5), and accuracy of 73.1% (95 %CI: 70.3–75.8). According to TI-RADS FNAB criteria, only 314 (30%) nodules would have undergone FNAB. Of them, 157 (50%) were classified as benign (Bethesda II), 45 (14.3%) as undetermined (Bethesda III or IV), and 51 (16.2%) as malignant (Bethesda V or VI). Of the remaining 729 nodules that did not meet FNAB criteria, 17 (2.3%) had Bethesda V or VI and underwent surgery. Of them, four (23%) were <1 cm in size (microcarcinomas), and eight (47.0%) remain in follow-up according to the TI-RADS criteria. Seven malignant cases would be missed (0.9%). Conclusion: ACR TI-RADS allows a significant decrease in the number of FNAB, increasing its diagnostic accuracy.